Implementation of Hamka's Philosophical Thoughts in Guidance and Counseling Services for the Elderly With Empty Nest Syndrome in Indonesia - Renidayati Renidayati; Yeni Karneli; Dina Sukma (Poltekita: Jurnal Ilmu Kesehatan, 2026)
Background: Empty nest syndrome is a psychosocial condition frequently experienced by older adults following children’s independence and departure from the household. This transition may lead to loneliness, loss of social roles, reduced meaning in life, and increased vulnerability to mental health problems. A holistic and culturally sensitive approach is therefore required. Hamka’s philosophical thought, emphasizing moral integrity, spiritual awareness, and social responsibility, offers a relevant framework to strengthen Guidance and Counseling (BK) services for older adults in Indonesia. Methods: This study employed a conceptual literature review of Hamka’s philosophical works, peer-reviewed articles on elderly mental health, and policy documents related to BK services. Thematic analysis was conducted to identify moral, ethical, and spiritual values relevant to the psychosocial needs of older adults and their potential application in counseling services. Results: The analysis identified core values including moral integrity, spiritual strengthening, character development, and redefinition of social roles in later life. These principles align with the psychosocial challenges of empty nest syndrome and can inform individual and group counseling interventions. Conclusion: Integrating Hamka’s philosophical values into BK services may enhance holistic mental health and psychosocial well-being among older adults within the Indonesian cultural context.